2021
DOI: 10.1021/acsami.1c08406
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Flexible Asymmetric Supercapacitor Paired with Indanthrone@Graphene Heterojunctions and MXene Electrodes

Abstract: The energy density formula illuminated that widening the voltage window and maximizing capacitance are effective strategies to boost the energy density of supercapacitors. However, aqueous electrolyte-based devices generally afford a voltage window less than 1.2 V in view of water electrolysis, and chemically converted graphene yields mediocre capacitance. Herein, multielectron redox-reversible, structurally stable indanthrone (IDT) π-backbones were rationally coupled with the reduced graphene oxide (rGO) fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…(E) Schematic illustration of the fabrication process for the Ti 3 C 2 T x MXene negative electrode (left section), IDT@rGO heterojunction positive electrode (right section), and the all‐solid‐state asymmetric supercapacitor device. Reproduced with permission: Copyright 2021, American Chemical Society 203 . (F) Schematic representation illustrating the fabrication process of asymmetric supercapacitor.…”
Section: Modification Of Mxene For Supercapacitormentioning
confidence: 99%
See 1 more Smart Citation
“…(E) Schematic illustration of the fabrication process for the Ti 3 C 2 T x MXene negative electrode (left section), IDT@rGO heterojunction positive electrode (right section), and the all‐solid‐state asymmetric supercapacitor device. Reproduced with permission: Copyright 2021, American Chemical Society 203 . (F) Schematic representation illustrating the fabrication process of asymmetric supercapacitor.…”
Section: Modification Of Mxene For Supercapacitormentioning
confidence: 99%
“…Xu et al 203 took the breakthrough of expanding the voltage window and maximizing capacitance by rationally coupling a multielectron redox reversible and structurally stable indolone π backbone with a reduced graphene oxide (GO) backbone in 2021 to form idt@rGo molecular heterojunction to fabricate a flexible asymmetric supercapacitor based on PVA/sulfuric acid hydrogel electrolyte, this flexible supercapacitor is based on idt@rGo heterojunction positive electrode and Ti 3 C 2 T x MXene (Figure 10D) negative electrode, steps as shown Figure 10E, 203 due to the rational construction of graphene and hetero molecules and the selection of MXene film as the paired negative electrode, which increases the electrode capacity and widens the assembled asymmetric supercapacitor, can output 1.6 V and high capacitance of 60 F/g for the whole device, reaching 17 Wh/kg at a power density of up to 8 kW/kg, and also has excellent multiplicity performance. The device also offers excellent multiplier performance, cycle stability, and mechanical flexibility.…”
Section: Modification Of Mxene For Supercapacitormentioning
confidence: 99%
“…18,19 However, the existing commercial SCs possess a very low energy density (∼3−9 W h kg −1 ), which restrains their exhaustive utilization. 12,20 Hence, the development of flexible SCs with good energy delivery at higher power densities along with other features like super flexibility, durability, high capacity, light weight, etc. is very much appropriate to fulfill the prospects of utilization in modern technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Several companies like Maxwell-Technologies (USA), ELTON (Russia), Nesscap (Korea), Nippon Chemicon (Japan), CAP-XX (Australia), etc. are currently engaged in the development of advanced SCs that can be applied in various fields. , However, the existing commercial SCs possess a very low energy density (∼3–9 W h kg –1 ), which restrains their exhaustive utilization. , Hence, the development of flexible SCs with good energy delivery at higher power densities along with other features like super flexibility, durability, high capacity, light weight, etc. is very much appropriate to fulfill the prospects of utilization in modern technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The device showed an energy density of 27.8 W h kg −1 in an operating voltage of 0−1.6 V. Boota et al 33 assembled a 2,5-dihydroxy-1,4benzoquinone@rGO//Ti 3 C 2 T x SC, which indicated an operating voltage of 0−1.4 V and an energy density of 40 W h kg −1 . Xu et al 34 prepared indanthrone@rGO heterojunction//Ti 3 C 2 T x SC, which showed a working voltage of 0−1.6 V and exhibited an energy density of 21.5 W h kg −1 .…”
Section: Introductionmentioning
confidence: 99%